RIOK3 promotes pancreatic ductal adenocarcinoma cell invasion and metastasis by stabilizing FAK. Issue 8 (August 2022) - Xu, Mengyuan; Fang, Lei; Guo, Xin; Qin, Henan; Sun, Rui; Ning, Zhen; Wang, Aman
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is an extremely aggressive cancer, characterized by a high metastatic burden. RIO Kinase 3 (RIOK3) has been shown to promote invasion and metastasis of PDAC by cytoskeleton remodeling, but the exact mechanism is still unknown. In this study, we analyzed transcriptome sequencing data from RIOK3 stable knockdown PANC-1 cells and TCGA-PDAC data and discovered that RIOK3 was substantially related to focal adhesion signaling in PDAC. Additionally, silencing RIOK3 dramatically decreased Focal Adhesion Kinase (FAK) protein expression and phosphorylation (Tyr397 and Tyr925 sites). Immunoprecipitation assay verified the interaction of RIOK3 and FAK. Furthermore, RIOK3 considerably increased the protein stability of FAK protein but not FAK-Y925F protein. The biological function of RIOK3 in increasing PDAC cell invasion and migration was shown to be dependent on FAK activation. Moreover, we discovered that RIOK3 mutations were mainly characterized by amplification. RIOK3 mRNA was found to be significantly elevated in PDAC tissues and was associated with a poor prognosis. Furthermore, RIOK3 mRNA was significantly upregulated in later T-stage, pre-existing lymph node metastases, and later pathological stage samples. Overall, our study found that RIOK3 promotes PDAC cell invasion and metastasis by stabilizing FAK protein expression and upregulating its phosphorylation. This also provides a new target for therapeutic modalities targeting FAK. Highlights: FAK activation is required for RIOK3 to promote PDAC cell invasion and metastasis. RIOK3 binds to and stabilizes the FAK protein. RIOK3 is highly expressed in PDAC tissues and associated with poor prognosis. Abstract : RIOK3; FAK; Pancreatic ductal adenocarcinoma; Invasion; Migration.